The participative processes in the management of the ecosystems in western Africa : a contribution to the environmental democracy - (:unkn) unknown (My University, 2015)
The participative processes basing on the principles of information and participation regarding environment contribute to the environmental democracy in Africa the West. This contribution is made beyond the implementation of these principles in the management of the ecosystems, by the research for an environmental social justice and the attempt to implement (operate) the principles of good governance in the service of the management of the ecosystems and the respect for human rights in the field of the environment. However, so that the participative processes make a better contribution to the environmental democracy in western Africa, it is necessary that the legal framework of the participation of the public is clarified. This legal framework concerns as well the access to the information, the procedures of participation of the public in the decision-making and in the management regarding environment, but especially to offer the possibility to the public to be listened by the justice or by of other one methods of payment of the disputes regarding environment and regarding management of the ecosystems.
Keywords: African Research